Effect of gamma irradiation on the viability and cellulase production of some filamentous fungi - Diep, Tran Bang; Thi Thom, Nguyen; Dang Sang, Hoang; Xuan An, Tran; Van Binh, Nguyen; Minh Quynh, Tran (Vietnam Journal of Biotechnology, 2020)
The motivation of our research is to examine the mutagenic effect of gamma irradiation on cellulase secretion of some filamentous fungi. The spore suspensions of Aspergillus sp. TTG and Trichoderma sp. VTCC were irradiated at dose ranging 0-2500 Gy under gamma Cobalt-60 source at Ha Noi Irradiation Center. The result showed that the survival rate of fungi decreases with the increasing dose. The radiation dose required to kill 90% of the total number of fungal spores (D10) of these strains was about 400 Gy. The viability of Aspergillus sp. TTG and Trichoderma sp. VTCC at 500 Gy were 0.46 % and 0.78%, respectively, while the number of survival spore decreased by 6.5-7.5 Log unit at the dose of 2500 Gy. By screening in PDA medium with the addition of CMC (carboxymethyl cellulose) and Congo red as an indicator of cellulose degradation, hundreds of colonies with higher hydrolysis capacity’s value (HC) compared to the initial strain were observed after irradiation. The colonies expressed the highest cellulose hydrolysis capacity with maximum HC value were obtained at dose range of 700-1500 Gy. It is important to notice the 5 potential mutants including 3 mutants of Aspergillus (TTG-700, TTG-1000 and TTG-1200) and 2 mutants of Trichoderma (VTCC-1000, VTCC-1500) demonstrated the higher CMCase secretion (1.78 – 2.48 times) compared to the wild types. After 5 generations, the enzyme productions of the mutants were fairly stable and there were no differences in growth rates and morphology of each generation. The result of this study is an evidence for using gamma irradiation to improve cellulase production in filamentous fungi.